Aspek Hukum Dalam Bertransaksi Jual Beli Secara Online - Mutriady, Anto (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In the implementation of buying and selling through the internet media consists of four processes, namely offering, accepting, paying, and sending. Article 1320 of the Civil Code states that the requirements for a valid agreement are the agreement of the parties, the capacity to make an agreement, a certain thing and a lawful cause can be applied to determine the validity of the electronic sales and purchase agreement. In this e-commerce practice, these requirements are not fully met, especially in terms of capacity, because it is difficult to know whether the parties in the e-commerce (especially the customer) are authorized to carry out a legal act (buying and selling via the internet) or not, as long as the transaction in e-commerce does not harm both parties, then the transaction is considered valid. So in this e-commerce practice, the requirements for a valid agreement in Article 1320 of the Civil Code are not fully met. The method used in this writing is the normative legal research type. The provisions regarding the rights and obligations of the seller and buyer above also apply to electronic sales and purchase transactions, although the seller and buyer do not meet directly, but the provisions regarding the rights and obligations of the seller and buyer must still be obeyed. Meanwhile, the settlement that can be done if there is a default in a sales and purchase agreement through Facebook media includes 2 alternative dispute resolution paths, namely Litigation and Non-Litigation. The Litigation path is through the courts, this path is considered less effective because often the time and costs that must be paid are not commensurate with the value of the loss of goods due to default, so the Non-Litigation path, especially the mediation path, is more in demand, because the costs are cheap, more effective and more 'familial' in resolving default cases.